SOME MORAL ISSUES RELATING TO THE ACTIVITIES OF CIVIL INTELLIGENCE SERVICE IN DEMOCRATIC STATES - Krzysztof Passella (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
The themes in the paper include different aspects of civil intelligence service activities in the context of its relations with the sphere of national security, international politics, business and science. The article refers to a number of moral problems, which are not alien to competition between intelligence agencies in the democratic countries, during processes of economics integration and political interactions in order to ensure common military and civil security. The paper shows a number of management processes and interactions among people working inside the structures of intelligence agencies. The discussion of the possible moral assessments of the intelligence has been provided, concerning point of social views and the special services provision in countries of democratic structure, this in particular, belonging to NATO and the European Union.